Management of Ureteric Small Bowel Fistula: A Case Report and Review of the Current Literature - Panagiota Fallon; Melissa Matthews; Abhisekh Chatterjee; Dimitrios Sapountzis; Nikolaos Chatzikrachtis; Katie McComb; Samuel Bishara; Ivo Donkov; Konstantinos Charitopoulos; Panagiotis Nikolinakos (Case Reports in Urology)
Conclusion: The treatment options for this ureteric small bowel fistula were limited. A lifelong nephrostomy was deemed unsuitable due to incompatibility with the patient’s profession, and surgical intervention was associated with significant complexity due to the patient’s history of malignancy and radiotherapy-related tissue changes. Therefore, a conservative strategy involving serial ureteric stent exchanges was pursued. Early recognition and individualised treatment of ureteric-enteric fistulas are essential, as timely intervention can significantly enhance prognosis and quality of life.